Kegiatan literasi informasi kesehatan seksual dan reproduksi pada Tenggara Youth Community - Reinanda, Adella Virginia; Damayani, Ninis Agustini; Sukaesih, Sukaesih (Jurnal Informatio, 2024)
Discourse on sexual and reproductive health remains taboo among adolescents, with prevalent misinformation and myths circulating in society. The Teman Bacarita program, initiated by the Tenggara Youth Community, was implemented online to enhance adolescent literacy on these issues. This study aims to analyze sexual and reproductive health information literacy activities through the online Teman Bacarita Program. The research employs a qualitative approach with a case study design. Data collection involved in-depth interviews, participatory observation, and literature review. Informants included two committee members and two participants of the Teman Bacarita Program. The analytical framework adopted Van Meter and Van Horn's program implementation model, encompassing six dimensions: (1) standards and objectives; (2) program resources; (3) characteristics of implementing agencies; (4) inter-organizational communication; (5) environmental conditions; and (6) implementer attitudes. Findings indicate that the online implementation of the Teman Bacarita Program as a sexual and reproductive health information literacy activity was relatively effective. Success indicators include clear program objectives, comprehensive standards, adequate human resources and infrastructure, effective communication between advisors and participants, competent implementing agents, and strong commitment from both advisors and participants despite challenges related to participants' social conditions and educational backgrounds.